The Effect of Investment and Labor on Economic Growth in North Luwu Regency - Surkati Akbar; Adnan Lukman Alhadif (Manunggal Halim Jaya, 2021)
The purpose of this study was to analyze the effect of investment and labor on the GRDP of North Luwu Regency and to find out which factors have the dominant influence on the GRDP of North Luwu Regency. This research was conducted in North Luwu Regency, where the data collection centers were the BPS Office (Central Statistics Agency) North Luwu Regency, as well as other official offices that could further refine the research data. The population in this study is all GRDP and investment, labor in North Luwu and the authors use secondary data (time series), there is no sample. The results of the study show that the effect of investment and labor on economic growth is positive. This means that if the investment is added it will increase economic growth. Likewise, if the workforce is added, it will be followed by an increase in economic growth. Through this research, the authors recommend this research to the local government so that to increase economic growth, factors that can have a positive impact are needed, including investment and labor factors.